Gambaran Kualitas Sarapan dan Konsentrasi Belajar Siswa Kelas 1 SDN Setramanah Subang - Sri Gustiani; Arief Budi Yulianti; Tryando Bhatara (Bandung Conference Series: Medical Science, 2024)
Abstract. Based on Basic Health Research in 2010, 45% of children had low quality breakfast. Breakfast is not just eating, it is important to pay attention to the quality and nutritional content contained in it. Breakfast is said to be of quality if the food consumed meets 15-30% of daily nutritional needs. Correspondence between the amount of carbohydrates, protein and fat in the body is very important, especially for children's growth and concentration at school. The aim of this research was to find out how the quality of breakfast and learning concentration of grade 1 students at SDN Setramanah Subang was described. This research uses a descriptive design. The sample was determined using total sampling with a total of 56 respondents. Research tools to measure breakfast quality and study concentration were obtained through interviews and questionnaires which had been tested for validity and reliability. The research results showed that the majority of respondents had breakfast quality in the just breakfast category and the least in the no breakfast category, while the learning concentration level of the majority of grade 1 students at SDN Setrmanah was in the age appropriate category (> 20 minutes). Abstrak. Berdasarkan Riset Kesehatan Dasar tahun 2010 terdapat 45% anak sarapan dengan kualitas yang rendah. Sarapan bukan hanya makan saja tetapi kualitas dan kandungan nutrisi yang terdapat di dalamnya perlu diperhatikan. Sarapan dikatakan berkualitas apabila makanan yang dikonsumsi telah memenuhi 15-30% kebutuhan gizi perharinya. Kesesuaian antara jumlah karbohidrat, protein, dan lemak dalam tubuh sangat penting terutama bagi pertumbuhan dan konsentrasi anak di sekolah. Tujuan penelitian ini dilakukan untuk mengetahui bagaimana gambaran kualitas sarapan dan konsentrasi belajar siswa kelas 1 SDN Setramanah Subang. Penelitian ini menggunakan desain deskriptif. Penentuan sampel menggunakan total sampling dengan jumlah 56 responden. Alat penelitian untuk mengukur kualitas sarapan dan konsentrasi belajar diperoleh melalui wawancara dan kuesioner yang sudah di uji validatas dan reliabilitasnya. Hasil penelitian menunjukkan sebagian besar responden memiliki kualitas sarapan dalam kategori sekedar sarapan dan yang paling sedikit terdapat dalam kategori tidak sarapan sedangkan tingkat konsentrasi belajar mayoritas siswa kelas 1 SDN Setrmanah masuk dalam kategori sudah sesuai usia (> 20 menit).